Mind the gap: Experimental tests to improve efficacy of fladry for nonlethal management of coyotes. (12th June 2019) - Young, Julie K.; Draper, John; Breck, Stewart
ABSTRACT: Coyotes ( Canis latrans ) are the top predator of livestock in the contiguous United States. Developing more effective nonlethal tools to prevent coyote depredation will facilitate coexistence between livestock producers and coyotes. Fladry is a nonlethal deterrent designed to defend livestock by creating a visual barrier to wolves ( C. lupus ). Fladry may also be effective with coyotes, but large gap spacing between flags may reduce its efficacy. To address this issue, we performed 2 experiments on captive coyotes using fladry modified to reduce gap spacing at the U.S. Department of Agriculture, Predator Research Facility in Millville, Utah, USA, during 2015–2016 and 2017–2018. In 2015–2016, we tested 2 styles for attaching flags (top‐knot and shower‐curtain) to the rope‐line that reduce gaps by preventing coiling of individual flags. In 2017–2018, we tested the efficacy of gap spacing (27.9 cm vs. 45.7 cm) between flags for preventing coyote crossings. For both tests, we compared the time until coyotes crossed the fladry between treatment types. We found no differences in time to crossing between the 2 attachment designs. In our second experiment, fladry with smaller gaps between flags had greater efficacy of preventing coyote crossings than did fladry with larger gaps. Our results also indicated that for each additional minute coyotes spent interacting with fladry overall (i.e., increased persistent behavior), survival of the barrier decreased. These results suggest that persistent coyotes may overcome neophobia more rapidly than coyotes that do not exhibit persistent behaviors. Furthermore, use of top‐knot fladry and coyote‐width spacing will increase protection of livestock from coyotes. © 2019 The Wildlife Society. Abstract : Our objective was to evaluate the efficacy of preventing coyotes (Canis latrans) from crossing fladry with new design modifications. Results show that using a top‐knot design with closer spacing between flags can increase efficacy, as measured by the time until crossing. Coyotes that exhibit persistence behavior crossed faster than coyotes exhibiting less persistence behavior.